Genetic types and provenance indication of clastic amphibole in the South Yellow Sea - Wang, Mengyao; Jin, Bingfu; Liu, Jian; Gao, Maosheng; Gao, Jianhua; Jia, Jianjun (Frontiers in Marine Science, 2024)
The main focus of studying sediment sources in marine areas is to determine the properties of clastic minerals originating from different rivers. Variations in the characteristics of clastic minerals occur due to differences in the types of source rocks within the watershed. Determining the source rock of clastic minerals in the marine area can improve the accuracy of provenance analysis. Electron probe microanalysis of 258 amphibole grains from six surface stations in the South Yellow Sea (SYS) was conducted to calculate the numerical and characteristic values of cations in the crystal structure. The results showed that amphibole in the SYS is mainly magnesiohornblende (52.2% ~ 81.4%) in the calcic amphibole subgroup, followed by tschermakite. The source rock types of amphibole are mainly different types of magmatic (ultrabasic, basic, and intermediate acidic) and metamorphic rocks. Amphibole derived from intermediate-acid intrusive rocks accounts for a large proportion (>40%). The genetic analysis of clastic amphibole in the SYS showed that most of the medium-acid invading amphibole belong to crust-mantle type, followed by mantle type. Most of the amphibole from metamorphic origins are of medium-low pressure type (± 80%). Combined with electron probe analysis of amphibole from the Huanghe River (the Yellow River, HH) and Changjiang River (the Yangtze River, CJ), the amphibole in the SYS exhibits characteristics inherited from these two rivers. The northern sea area has a strong resemblance to the sediments from the HH, while the southern area is more influenced by sediments supply from the CJ. The central area represents a mixed zone with a higher sediment supply from the HH. The clastic amphibole deduces the type of source rock in different watersheds, serving as a crucial link between the source rock, watershed, and marine area, providing a basis for provenance analysis.